Survey of the Use of Indonesian and Regional Languages in the Department of Geography Education, Faculty of Social Sciences, State University of Medan, Class of 2024 - Angraini Oktavia Hutapea; Terey Citha Siregar; Puput Gloria Zega; M Surip (BRIGHT VISION, 2026)
This study aims to determine the use of Indonesian and regional languages among students of the Geography Education Department, Faculty of Social Sciences, State University of Medan (UNIMED), Class of 2024. The study was conducted to determine the language most frequently used by students in formal and informal situations, as well as the factors influencing language choice when communicating on campus. The research method used was descriptive research with a quantitative approach. Data were obtained through the distribution of questionnaires using Google Forms to 10 Geography Education students, Class of 2024. The results showed that Indonesian was the most dominant language used, especially in academic activities such as class discussions, presentations, and formal communication because it was easier for all students to understand. Meanwhile, regional languages were still used in informal situations, especially when speaking with friends from the same region because they were considered more familiar and comfortable. Factors influencing language choice included the interlocutor, the communication situation, comfort, cultural identity, and communication effectiveness. This study shows that students are able to adapt their language use to the communication context without abandoning the function of regional languages as cultural identity.